CHEMICAL CHARACTERIZATION AND EVALUATION OF ANTIBACTERIAL, ANTIFUNGAL, ANTIMYCOBACTERIAL, AND CYTOTOXIC ACTIVITIES OF Talinum paniculatum - REIS, Luis F.C. DOS; CERDEIRA, Cláudio D.; PAULA, Bruno F. DE; SILVA, Jeferson J. da; COELHO, Luiz F.L.; SILVA, Marcelo A.; MARQUES, Vanessa B.B.; CHAVASCO, Jorge K.; ALVES-DA-SILVA, Geraldo (Revista do Instituto de Medicina Tropical de São Paulo, 2015)
In this study, the bioactivity of Talinum paniculatum was evaluated, a plant widely used in folk medicine. The extract from the T. paniculatum leaves (LE) was obtained by percolation with ethanol-water and then subjecting it to liquid-liquid partitions, yielding hexane (HX), ethyl acetate (EtOAc), butanol (BuOH), and aqueous (Aq) fractions. Screening for antimicrobial activity of the LE and its fractions was evaluated in vitro through broth microdilution method, against thirteen pathogenic and non-pathogenic microorganisms, and the antimycobacterial activity was performed through agar diffusion assay. The cytotoxic concentrations (CC90) for LE, HX, and EtOAc were obtained on BHK-21 cells by using MTT reduction assay. The LE showed activity against Serratia marcescens and Staphylococcus aureus, with Minimum Inhibitory Concentration (MIC) values of 250 and 500 µg/mL, respectively. Furthermore, HX demonstrated outstanding activity against Micrococcus luteus and Candida albicans with a MIC of 31.2 µg/mL in both cases. The MIC for EtOAc also was 31.2 µg/mL against Escherichia coli. Conversely, BuOH and Aq were inactive against all tested microorganisms and LE proved inactive against Mycobacterium tuberculosisand Mycobacterium bovisas well. Campesterol, stigmasterol, and sitosterol were the proposed structures as main compounds present in the EF and HX/EtOAc fractions, evidenced by mass spectrometry. Therefore, LE, HX, and EtOAc from T. paniculatumshowed potential as possible sources of antimicrobial compounds, mainly HX, for presenting low toxicity on BHK-21 cells with excellent Selectivity Index (SI = CC90/MIC) of 17.72 against C. albicans.